Mob Politics: The Political Influence of the Circus Factions in the Eastern Empire from the Reign of Leo I to Heraclius (457-641) - Main, Robert W. (Université d'Ottawa / University of Ottawa, 2013)
This paper seeks to continue the research started by scholars such as W. Liebeschuetz and P. Bell in order to challenge the traditional argument put forth by Al. Cameron, namely that the circus factions did not have a political role in society. The objective of this study is to examine the political importance of the circus factions from the reign of Anastasius (491-518) to Heraclius (610-641). Furthermore, it explores the political motivations behind the factions’ violent behaviour, the evidence for their involvement in the military, and their role in accession ceremonies. The methodology includes establishing a typology for sixth century riots, an examination of the hippodrome and its role as a medium between people and emperor, tracing the shift in the focus of imperial ideology, and a re-evaluation of the primary sources, with a focus on the literary and epigraphic evidence, to determine if there was a political aspect to the factions. The study concludes that Cameron did undervalue the factions’ political importance and outlines the conditions that were influential in their rise in importance.
Keywords: Rome; Circus Factions; Factions; Constantinople; imperial ceremonies; eastern empire; riots; hippodrome; chariot racing; militias; Byzantine; Byzantium